UNCTAD's investment policy reviews : key policy lessons - Dupasquier, Chantal (2012)
Summarises the lessons learnt from the UNCTAD Investment Policy Review (IPR) programme and highlights issues and challenges for policy and corporate strategy on cross-border investment.